Features of competitive innovative systems of the Republic of Kazakhstan under globalization - Baimbetova, A.B.; Gizzatzhanova А.G.; Muhiyaeva, D.M.; Aykupesheva , D.M. (BUKETOV BUSINESS REVIEW, 2017)
This article considers about ways that improve the competitiveness of innovative system of the Republic of Kazakhstan in the context of globalization. Competitiveness in an industry or service sector is very important. It seems that welfare of the people of Kazakhstan is improving during the global recovery and the innovative development of the state. Therefore, considered question in the articles is based on the revival and development of the national innovation system, modernization of the legal regulations and the development of strategies and innovative potential of cooperation between countries, opportunities and risks assessment, as well as clusters, which bring them together. Nowadays, optimal and effective service of production or service enterprises allows to overtake or to stand out in the level of competition and cooperation. Thus, this kind of actions give an opportunity to form new models on the market, national innovation systems; to spread information and knowledge; to strengthen the regulatory and legal framework. Innovative potential of cooperation of countries stands out by their future development and change. The joining of the Republic of Kazakhstan to the rank of many developed countries, the effective development of innovation sector, which shows economical growth, is observed in the article. The result of innovative services based on the competitiveness of the national economy. Considered the entry of the Republic of Kazakhstan in a number of developing countries and the rationale for effective development of innovative sphere in the conditions of globalization. The result of innovative activity, national economy is based on the existence of competitiveness.